Indonesia’s Rationality in Improving The Economy Through BRICS: A World System Theory Approach - Pambagyo, Wahyu; Herningtyas, Ratih (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study analyzes Indonesia's strategic decision to join BRICS (Brazil, Russia, India, China, and South Africa) under the leadership of President Prabowo Subianto on January 6, 2025. This move reflects Indonesia's efforts to strengthen economic growth, global influence, and diplomatic capacity amid the dynamics of a multipolar world. This study uses Immanuel Wallerstein's World-System Theory approach to explain Indonesia's rationale in making this decision. The methods used are qualitative and descriptive through literature and policy analysis to examine the background, Indonesia's economic relations with BRICS, investment, and foreign policy. The results show that Indonesia, as a semi-peripheral country, is trying to move up in the world economic system and expand its trade network by taking advantage of opportunities from BRICS. Indonesia-BRICS trade is valued at USD 150 billion in 2024, while energy dependence remains at 50% on imports and 81% on fossil-based electricity. Through BRICS and institutions such as the New Development Bank and the Contingent Reserve Arrangement (CRA), Indonesia has the potential to access alternative funding and expand its export markets.